Salvianolic Acid Modulates Physiological Responses and Stress-Related Genes That Affect Osmotic Stress Tolerance in Glycine max and Zea mays - Kazerooni, Elham Ahmed; Al-Sadi, Abdullah Mohammed; Rashid, Umer; Kim, Il-Doo; Kang, Sang-Mo; Lee, In-Jung (Frontiers in Plant Science, 2022)
Drought is a serious threat worldwide soybean and maize production. This study was done to discern the impact of salvianolic acid treatment on osmotic-stressed soybean (Glycine max L.) and maize (Zea mays L.) seedlings from the perspective of physiochemical and molecular reactions. Examination of varied salvianolic acid concentrations (0, 0.1, 1, 5, 10 and 25 μM) on soybean and maize seedling growth confirmed that the 0.1 and 1 μM concentrations, respectively, showed an improvement of agronomic traits. Likewise, the investigation ascertained how salvianolic acid application could retrieve osmotic-stressed plants. Soybean and maize seedlings were irrigated with water, or 25% PEG for 8 days. The results indicated that salvianolic acid application promoted survival of the 39-day-old osmotic-stressed soybean and maize plants. The salvianolic acid-treated plants retained high photosynthetic pigments, protein, amino acid, fatty acid, sugar, antioxidant contents and demonstrated low hydrogen peroxide, and lipid metabolism contents under osmotic stress. Gene transcription pattern certified that salvianolic acid application led to raised expression of GmGOGAT, GmUBC2, ZmpsbA , ZmNAGK, ZmVPP1, and ZmSCE1d genes and diminished expression of GmMIPS2, GmSOG1, GmACS, GmCKX, ZmPIS, and ZmNAC48 genes. Together, our results indicate the utility of salvianolic acid to enhance the osmotic endurance of soybean and maize.